Correlation of Teacher Interpersonal Interaction and Classroom Emotional Climate in Biology Learning, Merdeka Curriculum - Savira Nuraini; Zulfiani (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2026)
In recent years, the national curriculum has shifted from the 2013 Curriculum to the Merdeka Curriculum, requiring adjustments in the learning process. A key factor in its success is the interaction between teachers and students, which supports learning goals and outcomes. Such interaction is crucial in Biology, which demands effective communication and strong teacher-student relationships. This study aims to analyze the relationship between teacher interpersonal interaction and the emotional climate of the classroom in Biology learning under the Merdeka Curriculum. The research used a quantitative correlational method. The sample consisted of 41 eleventh-grade science students from public high schools in West Bogor City. Instruments used were the QTI (Questionnaire on Teacher Interaction) and Q-CEC (Questionnaire on Classroom Emotional Climate). Data were analyzed using Pearson product-moment correlation with IBM SPSS Statistics version 26. Results showed a positive and significant relationship between teacher interpersonal interaction and classroom emotional climate, contributing 14.9%. Interactions marked by empathy, emotional support, and effective communication, especially from teachers with Tolerant and Authoritative profiles, help create a conducive classroom atmosphere that supports learning. Therefore, the quality of teacher interpersonal interaction is a key factor in fostering a positive emotional climate in Biology learning under the Merdeka Curriculum.